(untitled) (Revista Inclusiones, 2020)
The article analyzes the current state and prospects of regulation of the market of derivative financial instruments (derivatives) in the Russian Federation. The financial derivatives market in Russia is relatively young, and as a result, many of its aspects are not clearly regulated by Russian law, which naturally creates numerous problems for participants. The purpose of this study is to analyze the legal regulation of the turnover of derivative financial instruments and offer recommendations for improving the regulatory framework to solve the identified problems. The article discusses the prerequisites for the emergence of legal regulation of the financial derivatives market, the initial content, and recent changes. The legislative basis of the new system has been shown, the main legal acts and subjects of regulation have been listed.